Satellite tagging insights into the seasonal movements and behavior of Mediterranean spearfish (Tetrapturus belone, Istiophoridae) - Malara, Danilo; Battaglia, Pietro; Arostegui, Martin C.; Dale, Jonathan J.; Block, Barbara A.; Braun, Camrin D.; Brogna, Massimo; Greco, Silvestro; Romeo, Teresa (Frontiers in Marine Science, 2024)
The Mediterranean spearfish (Tetrapturus belone) is a highly migratory predator, also exploited by commercial and recreational fisheries although its catches are poorly reported. The fishing pressure on this species is currently unknown because catch and landing data are fragmentary. Furthermore, more ecological information (e.g. migratory movements) is needed to establish eventual management measures, and ICCAT has not examined the population status yet. Understanding species migratory movements is crucial for addressing conservation challenges and supporting management decisions. In this study we investigated the migratory movements, seasonal patterns, vertical behavior, and thermal preference of T. belone, with the aim to improve information on its ecology and behavior. Overall, six individuals were tagged in the Strait of Messina and Tyrrhenian Sea with pop-up satellite tags and their movements were mainly restricted to the central Mediterranean. Utilization distributions derived from geolocation revealed an overall and seasonal importance of the Tyrrhenian Sea and Strait of Sicily, as well as variability in winter habitat use. While the fish exhibited similar depth preference, spending the majority of time at depths ≤ 10 m, we observed that the Mediterranean spearfish is also able to perform sporadic deep dives below 200 m. Vertical movement showed a bimodal pattern common in other billfish species, characterized by occupation of shallower, warmer waters during the night and deeper, cooler waters during the day. This research increases knowledge on the migration ecology and habitat preference of T. belone which is important for management of this understudied species.